Reconocimiento de las emociones básicas como un factor determinante para la disminución del miedo escénico en el desarrollo de actividades escolares en niños de 10 años de la Unidad Educativa Vicente Rocafuerte. - Capuz Tiban, Susana Margarita (2022)
The present degree work focuses on the basic emotions of children and stage fright during the development of various school activities. Through the study of this problem, a proposal for intervention was generated. In order to create a positive environment where active learning is stimulated considering the identification and management of emotions. It seeks at all costs the reduction of stage fright in the student for better interaction between their peers and the teacher. This research aims to identify basic emotions as a determining factor for the reduction of stage fright in the development of school activities in 10-year-old children of the Vicente Rocafuerte Educational Unit. The methodology implemented in this research product, which maintains a qualitative approach to strengthen knowledge, was put into practice various methods such as; deductive-inductive, descriptive and 9 bibliographic. An interview was used with thirty-two sixth-year EGB students. Finally, according to the analysis and interpretation of data, it is concluded that recognition of basic emotions is essential for the socio-affective development of the child. And stage fright is the main communication barrier in the classroom. What limits the optimal learning of the student